Job Characteristics, Affective Commitment, and Turnover Intentions: A Dual-Theory Examination of Generation Z - Yen Thi Hai Mac; Cuong Thi Tran (Emerging Science Journal, 2026)
This study investigates the extent to which core job characteristics—autonomy, task identity, task significance, and skill variety—influence affective commitment and turnover intentions among Generation Z employees in Vietnam. Based on the Job Demands–Resources (JD-R) and Conservation of Resources (COR) theoretical frameworks, the study seeks to elucidate how early-career employees interpret job resources within a collectivist, hierarchical, and resource-constrained environment. A structured quantitative design was employed, drawing on survey data from 312 Gen Z respondents across diverse organizational settings. Measurement validity and reliability were established via Confirmatory Factor Analysis and Cronbach’s Alpha, while hypotheses were tested using Structural Equation Modeling (SEM). Empirical findings reveal that task identity exerts a negative influence on affective commitment, whereas autonomy, task identity, and skill variety are positively associated with turnover intentions. Task significance demonstrates no significant effect on either outcome. Conversely, affective commitment emerges as a strong inverse predictor of turnover intentions, underscoring its role as a stabilizing psychological resource. This research contributes to the existing literature by integrating JD-R and COR theories to challenge the presumed universality of job resource effects. It underscores the contextual sensitivity of job design, particularly for younger cohorts in emerging markets. The findings offer practical implications for designing culturally and generationally responsive retention strategies.